Postoperative Intraocular Pressure Changes After Cataract Surgery Using Phacoemulsification Technique at H. Abdul Manap Regional Hospital Jambi During July–September 2025 - Hanum Chaira Bahri Aeswarani; Vonna Riasari; Hasna Dewi; Gita Mayani; Lipinwati Lipinwati (International Journal of Health and Social Behavior, 2026)
Background: Phacoemulsification is the standard therapy for cataracts; however, postoperative changes in intraocular pressure (IOP) may lead to complications. This study observed changes in IOP on the first and sixth postoperative days and the associated risk factors. Objective: To analyze changes in IOP after phacoemulsification and determine the frequency of related risk factors. Methods: A prospective cohort study was conducted on 31 eyes from 27 patients who underwent uncomplicated phacoemulsification at H. Abdul Manap Regional Hospital Jambi from July to September 2025. IOP was measured on postoperative day 1 and day 6. Data were analyzed using the Wilcoxon Signed Rank test with a significance level of p < 0.05. Results: The majority of patients were male (68%) and aged 60–74 years (48%). Mean IOP decreased significantly from 17.16 mmHg on postoperative day 1 to 14.00 mmHg on day 6 (p = 0.001). Knowledge of wound care and medication adherence were considered good. Corneal edema was observed in 4 cases on day 1 and was not observed on day 6. Postoperative inflammatory symptoms also decreased. Conclusion: Phacoemulsification resulted in a significant reduction in IOP and demonstrated good postoperative outcomes.